1995
DOI: 10.1121/1.413112
|View full text |Cite
|
Sign up to set email alerts
|

Temporal envelope and fine structure cues for speech intelligibility

Abstract: This paper describes a number of listening experiments to investigate the relative contribution of temporal envelope modulations and fine structure to speech intelligibility. The amplitude envelopes of 24 1/4-oct bands (covering 100-6400 Hz) were processed in several ways (e.g., fast compression) in order to assess the importance of the modulation peaks and troughs. Results for 60 normal-hearing subjects show that reduction of modulations by the addition of noise is more detrimental to sentence intelligibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
83
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(93 citation statements)
references
References 0 publications
9
83
1
Order By: Relevance
“…Although the perception of speech has been proposed to rely on the detailed spectral information in the acoustic signal (see Stevens, 1998;Diehl et al, 2004), several studies have demonstrated that accurate recognition persists despite severe spectral degradation (van Tasell et al, 1987;van Tasell et al, 1992;Shannon et al, 1995;Drullman, 1995;Shannon et al, 1998;Smith et al, 2002). This is particularly relevant for cochlear implants, in which spectral information is limited due to a finite number of electrodes.…”
Section: Introductionmentioning
confidence: 97%
“…Although the perception of speech has been proposed to rely on the detailed spectral information in the acoustic signal (see Stevens, 1998;Diehl et al, 2004), several studies have demonstrated that accurate recognition persists despite severe spectral degradation (van Tasell et al, 1987;van Tasell et al, 1992;Shannon et al, 1995;Drullman, 1995;Shannon et al, 1998;Smith et al, 2002). This is particularly relevant for cochlear implants, in which spectral information is limited due to a finite number of electrodes.…”
Section: Introductionmentioning
confidence: 97%
“…As acknowledged by Cooke (2006), the glimpse detection model used in his study to estimate the local SNR defining a glimpse was based on spectrotemporal excitation patterns lacking a representation of the temporal fine structure (TFS) of auditory nerve responses to sound. However, additional studies reveal that TFS play a role in speech intelligibility in noise (Drullman, 1995) and that speech masking release is strongly reduced and sometimes disappears when TFS information is absent or poorly perceived (e.g., Nelson et al, 2003;Qin and Oxenham, 2003;Stickney et al, 2005;Zeng et al, 2005;Fü llgrabe et al, 2006;Lorenzi et al, 2006b; for psychoacoustic evidence, see also Moore and Glasberg, 1987), suggesting that this temporal cue signals the presence of speech information into noise valleys. The goal of the present study is therefore to examine release from masking as a function of modulation depth, with and without TFS cues.…”
Section: Introductionmentioning
confidence: 98%
“…For example, the ability to discriminate the interval and duration of sounds is critical for speech processing (Liberman et al 1956;Scott 1982;Drullman 1995;Shannon et al 1995;Aasland & Baum 2003). However, the neural mechanisms involved even in a simple temporal task, such as interval discrimination, remain unknown.…”
Section: Introductionmentioning
confidence: 99%